Bacterial resistance due to indiscriminate use of the carbapenems meropenem and imipenem: an integrative review (Research, Society and Development, 2022)
Antimicrobials are substances that kill or inhibit the growth of microorganisms and their prescription in hospitals is mainly based on the effectiveness of the drug. Carbapenems are antimicrobials resistant to the action of β-lactamases and AmpC. Meropenem and imipenem are antibiotics that belong to this class and represent the ß-lactams with the highest antimicrobial potency, meropenem has a superior in vitro activity against gram-negatives, but imipenem is slightly more active against gram-positives. Objective: For him, the objective was to describe the occurrence of bacterial resistance due to the discriminated use of the carbapenems mer openem and imipenem, causing bacterial multi-resistance. Method: integrative study of Bibliography review in LILACS, PUBMED/MEDELINE and SCIELO databases, between 2012 and 2022. Select 75 articles, from the 10 codes used in the elaboration of the work. The results that bacterial multidrug resistance have created in recent years of infection by infection by multidrug resistant bacteria and by multidrug resistant bacteria, due to the unnecessary use of antibiotics and the indiscriminate challenge to select microorganisms, to which the influence of others of resistance leads, putting at risk human health, which leads to an extension of hospitalization days, increased costs and higher mortality, you escape new therapeutic options for the treatment of infections with multidrug-resistant bacteria. Concluding that prescriptions play an important role in promoting the rational use of antimicrobials, it is not enough to have an accurate diagnosis and an adequate selection of the antimicrobial if the prescription is not rigorously elaborated and complete in all its aspects. It is necessary that the use of antibiotics is indicated, as much for the health as for the bacterial population, as the indication that it is effective against antibiotics against infectious diseases.